(untitled) (UNIZIK Journal of Marketing, 2025)
This research is on the effects of adopting International Financial Reporting Standards (IFRS) on the quality of financial reporting among publicly traded manufacturing firms in Nigeria. The study was focused on 43 manufacturing companies listed on the Nigerian Exchange Group (NXG). From this group, fifteen companies were selected as the sample, based on their adherence to IFRS since 2012. Data for this study was sourced from the annual reports and financial statements of these fifteen companies, covering the period from 2013 to 2022. The analysis utilized regression techniques to evaluate the data. The findings from the regression analysis indicated that IFRS adoption has a significant positive impact on the value relevance of financial information, meaning that financial reports under IFRS are more useful for decision-making by investors and other stakeholders. However, the adoption of IFRS was found to have a significant negative effect on earnings management, suggesting that IFRS reduces the ability of companies to manipulate their earnings figures. On the other hand, the study found that IFRS had a negative but statistically insignificant effect on the timely recognition of losses, indicating that while IFRS may influence how losses are reported, the impact is not strong enough to be considered significant in this context. In light of these findings, the study recommends, among others that the information environment in Nigeria be improved to ensure that various stakeholders including investors, financial analysts, government agencies, regulatory bodies, individual investors, and researchers have access to comprehensive and transparent financial information from companies listed on the NXG.